Korelasi Kadar Troponin I dengan Serum Glutamic Oxaloacetic Transaminase (SGOT) dan Low Density Lipoprotein (LDL) Pada Penderita Penyakit Jantung Koroner Di RSUD Haji Provinsi Jawa Timur - Amania, Salsabila; Handayati, Anik; Museyaroh (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Coronary Heart Disease (CHD) is a condition caused by atherosclerosis, which leads to reduced blood supply to the heart muscle. This condition occurs due to the buildup of plaques resulting form elevated levels of LDL.  Atherosclerosis can trigger myocardial infarction, leading to heart muscle damage and the release of biomarkers such as Troponin I and Serum Glutamic Oxaloacetic Transaminase (SGOT). Objectives: This Study aims to determine the correlation between Troponin I levels and SGOT as well as LDL levels in patients with CHD at Haji General Hospital in East Java Province. Materials and Methods: This study used an analytical observational study with a cross-sectional and purposive sampling. Results: The study results show that the majority of participants were aged 46–65 years (57%) and male (57%). Most patients had high Troponin I levels (70%), normal SGOT levels (63%), and high LDL levels (100%). The correlation analysis using the Spearman test showed a statistically significant correlation between Troponin I and SGOT levels with p value 0.046 and correlation coefficient r= 0.367, but the correlation between Troponin I and LDL levels was not statistically significant with p value 0.330 and correlation coefficient = 0.184. Conclusions:  The study found a correlation between Troponin I and SGOT in patients with CHD and no correlation between Troponin I and LDL in patients with CHD.